Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Using separation of variables Solve $$\frac{dy}{dx} = 3y +1.$$ My final answer I got was: $$y = \pm C \frac{e^x}{3} - \frac{1}{3}.$$

But I don't how to take the derivative of that to get it back to my orig problem

share|improve this question
    
"But I don't how to take the derivative of that" - What's the derivative of $e^x$? A constant? –  J. M. Oct 5 '11 at 16:24
    
But I don't how to take the derivative of that, to get it back to 3y +1. If you integrate something the derivative of that integral is the problem you started with yes? Well that is what I am trying to do (1/3)e^x != 3y+1 –  domshyra Oct 5 '11 at 16:36
1  
There is a mistake in your integration, which probably came when you integrated $dy/(3y+1)$. The result should have been $\frac{1}{3} \ln(|3y+1|)$ (plus a constant). I think you left out the $1/3$ in front. So the solution you give to the DE is not right. It should involve $e^{3t}$. –  André Nicolas Oct 5 '11 at 16:37
    
Oh right!!! because I would use U-sub and yeah. Thank you!!! –  domshyra Oct 5 '11 at 16:48
    
Now it will pass the differentiation test! Differentiation for most people is (after a while) easy and accurate. So checking whether a claimed solution works is usually a good idea. –  André Nicolas Oct 5 '11 at 16:52
show 1 more comment

1 Answer

up vote 4 down vote accepted

First, note that a constant divided by $3$ is just a constant, so you could rewrite what you have without the fraction. Also, plus or minus a constant is just a constant. So you could rewrite your solution as $$y = Ce^x - \frac{1}{3}.$$

To check, you just take the derivative: $C$ is a constant, so $$\frac{dy}{dx} = \frac{d}{dx}\left(Ce^x - \frac{1}{3}\right) = C\frac{d}{dx}e^x - \frac{d}{dx}\frac{1}{3} = Ce^x.$$

Then you compute $3y + 1 = 3Ce^x - 1 + 1 = 3Ce^x$.

This is not the same as $\frac{dy}{dx}$, so this is not a correct answer.

And, no, it wasn't my "simplifications" that did you in: $$\frac{d}{dx}\left( \pm \frac{Ce^x}{3} - \frac{1}{3}\right) = \pm\frac{C}{3}\frac{d}{dx}e^x = \pm\frac{C}{3}e^x,$$ and $$3\left(\pm\frac{Ce^x}{3}-\frac{1}{3}\right) + 1 = \pm Ce^x\neq \pm\frac{Ce^x}{3}.$$

So in fact, you did a mistake in your derivation.

From $$\frac{dy}{dx} = 3y+1,$$ we must consider the possibility that $3y+1=0$; this will occur if $y=-\frac{1}{3}$; that is one possible solution.

If $3y+1\neq 0$, then separating variables we get $$\frac{dy}{3y+1} = dx,$$ and integrating both sides, we have $$\int\frac{dy}{3y+1} = \int\,dx.$$ To do the integral on the left, we let $u=3y+1$; then $du = 3dy$, so $\frac{1}{3}du = dy$. Hence $$\int\frac{dy}{3y+1} = \int\frac{\frac{1}{3}du}{u} = \frac{1}{3}\int\frac{du}{u} = \frac{1}{3}\ln|u|+C = \frac{1}{3}\ln|3y+1|+C;$$ so, consolidating constants, we have: $$\begin{align*} \int\frac{dy}{3y+1} &= \int\,dx\\ \frac{1}{3}\ln|3y+1| &= x+C&&C\text{ an arbitrary constant}\\ \ln|3y+1| &= 3x + D&&D\text{ an arbitrary constant}\\ e^{\ln|3y+1|} &= e^{3x+D}\\ |3y+1| &= e^De^{3x}\\ |3y+1| &= Ae^{3x} &&A\text{ a positive constant}\\ 3y+1 &=\pm Ae^{3x} &&A\text{ a positive constant}\\ 3y+1 &= Be^{3x} &&B\text{ a non-zero constant}\\ 3y &= Be^{3x} - 1\\ y &= \frac{B}{3}e^{3x} - \frac{1}{3}\\ y &= Ke^{3x} - \frac{1}{3} &&K\text{ a non-zero constant} \end{align*}$$ I set $D=3C$, still a constant, then $A=e^D$, a positive constant (because $e^D$ is always positive); then $B=\pm A$, a nonzero constant (because $A$ is never zero, so $B$ is never zero); and finally $K=\frac{B}{3}$, a nonzero constant (because $B$ is never zero).

So putting it together with the special case considered before, we have that the solutions are: $$\text{Either }y=-\frac{1}{3}\quad\text{or}\quad y = Ke^{3x}-\frac{1}{3}\text{ with }K\text{ non-zero.}$$ Then we may realize that if we allow $K=0$, then we get the special case, so we can summarize the two cases by saying $$ y = Ke^{3x} - \frac{1}{3},\quad K\text{ an arbitrary constant.}$$

Now take derivatives and plug in to verify this is correct.

share|improve this answer
2  
wow you went all out in this explanation, and It was very helpful. Thank you very much! I really, really appreciate it! Thanks again!!! –  domshyra Oct 5 '11 at 16:59
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.